2021
DOI: 10.1038/s41598-021-91739-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic modifications of F1 offspring’s sperm cells following in utero and lactational combined exposure to nicotine and ethanol

Abstract: It is well established that maternal lifestyle during pregnancy and lactation affects the intrauterine programming of F1 offspring. However, despite the co-use of alcohol and nicotine is a common habit, the effects of exposure to both substances on the reproductive system of F1 male offspring and the underlying mechanisms of developmental programming have not been investigated. The present study aimed to examine pre- and postnatal concurrent exposure to these substances on genetic and epigenetic alterations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…Complex molecular regulations during in utero development are a result of interactions between genetic and epigenetic. Maternal lifestyle [ 23 , 24 ], such as a dietary supplement with phytoestrogens is one of the environmentally epigenetic effect elements that could affect developmental programming processes [ 26 ]. However, maternal steroid hormone-binding protein (SHBG) and fetal α-fetoprotein are the main modifiers of fetal exposure to phytoestrogens that may protect the fetus partly from the destructive effects of exogenous estrogens such as phytoestrogens [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Complex molecular regulations during in utero development are a result of interactions between genetic and epigenetic. Maternal lifestyle [ 23 , 24 ], such as a dietary supplement with phytoestrogens is one of the environmentally epigenetic effect elements that could affect developmental programming processes [ 26 ]. However, maternal steroid hormone-binding protein (SHBG) and fetal α-fetoprotein are the main modifiers of fetal exposure to phytoestrogens that may protect the fetus partly from the destructive effects of exogenous estrogens such as phytoestrogens [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The synthesized cDNA was stored at -20 °C until use. Three replicates of qRT-PCR reactions were performed on a mixture consisted of 5 μl syber green Master Mix (Genaxxon bioscience, Ulm, Germany), 1 μl of each specific primers [ 23 ] (Table 1 ), and 2 μl of cDNA in a final volume of 10 μl. The program of q real-time PCR was as follows: initial denaturation at 95 °C for 40 s, followed by 35 cycles of denaturation at 95 °C for 20 s, 60 °C for 30 s, and final extension at 72 °C for 30 s using a Light Cycler Real-Time PCR System (MIC, Queensland, Australia).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although human health is impaired by environmental exposure at any time, the potential effects of exposures during pregnancy are magnified during the most critical developmental period for male fetal development [ 151 ]. Maternal exposures to low dietary protein, high milk, alcohol, and nicotine [ 136 ] may adversely affect male fertility through epigenetic mechanisms [ 151 ]. Epidemiological and experimental studies have shown that exposure to a maternal low dietary protein during pregnancy reduces male fertility in adult male rats [ 130 ].…”
Section: Multisystem Diseasesmentioning
confidence: 99%